Global FKRP Registry: observations in more than 300 patients with Limb Girdle Muscular Dystrophy R9. Issue 5 (28th April 2020) - Murphy, Lindsay B.; Schreiber‐Katz, Olivia; Rafferty, Karen; Robertson, Agata; Topf, Ana; Willis, Tracey A.; Heidemann, Marcel; Thiele, Simone; Bindoff, Laurence; Laurent, Jean‐Pierre; Lochmüller, Hanns; Mathews, Katherine; et al.
Abstract: Objective: The Global FKRP Registry is a database for individuals with conditions caused by mutations in the Fukutin‐Related Protein ( FKRP ) gene: limb girdle muscular dystrophy R9 (LGMDR9, formerly LGMD2I) and congenital muscular dystrophies MDC1C, Muscle–Eye–Brain Disease and Walker–Warburg Syndrome. The registry seeks to further understand the natural history and prevalence of FKRP‐related conditions; aid the rapid identification of eligible patients for clinical studies; and provide a source of information to clinical and academic communities. Methods: Registration is patient‐initiated through a secure online portal. Data, reported by both patients and their clinicians, include: age of onset, presenting symptoms, family history, motor function and muscle strength, respiratory and cardiac function, medication, quality of life and pain. Results: Of 663 registered participants, 305 were genetically confirmed LGMDR9 patients from 23 countries. A majority of LGMDR9 patients carried the common mutation c.826C > A on one or both alleles; 67.9% were homozygous and 28.5% were compound heterozygous for this mutation. The mean ages of symptom onset and disease diagnosis were higher in individuals homozygous for c.826C > A compared with individuals heterozygous for c.826C > A. This divergence was replicated in ages of loss of running ability, wheelchair‐dependence and ventilation assistance; consistent with the milder phenotype associated with individuals homozygous for c.826C > A. In LGMDR9 patients, 75.1% were currently ambulant and 24.6%, nonambulant (unreported in 0.3%). Cardiac impairment was reported in 23.2% (30/129). Interpretation: The Global FKRP Registry enables the collection of patient natural history data, which informs academics, healthcare professionals and industry. It represents a trial‐ready cohort of individuals and is centrally placed to facilitate recruitment to clinical studies.